Electrostatic attraction type graphene conductive coating solution and preparation method thereof
By adding anionic and cationic surfactant to the graphene conductive coating solution, and undergoing magnetic stirring and ultrasonic crushing, the problems of unstable dispersion and unobvious improvement of the conductive properties of the coating solution are solved, and graphene and copper are realized The firm bonding of the wire and the improved conductivity of the electrically conductive properties.
Patent Information
- Application Number
- CN202411238244.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
In the preparation process of carbon conductive coating solution, the dispersion of the coating solution is unstable, and the conductive performance is not significantly improved. After coating, the surface roughness of the graphene copper composite wire is high, the graphene sheet layer is raised, the bond is not firm, and it is easy to fall off. The problem.
The electrostatically attractive graphene conductive coating solution is used, which contains graphene, anionic surfactant and cationic surfactant. Through magnetic stirring and ultrasonic crushing, micelles and ionization are formed to attract each other, reducing the van der Waals force between graphene sheets. , improve the bonding strength and continuity between graphene and copper wire.
It significantly improves the bonding firmness and conductivity of graphene and copper wire, reduces the surface roughness of the coating, avoids the fall of the graphene sheet layer, builds a stable and continuous conductive network, and improves the current carrying capacity of the copper wire and Conductive properties.
Smart Images

Figure CN119307123A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive coatings, and in particular to an electrostatic attraction type graphene conductive coating solution and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology in today's era, the conductive properties of traditional alloyed metal materials and composite materials can hardly meet the technological development needs of future high-end fields. Therefore, the development of new high-conductivity materials has become a key research and development project for enterprises and even the country in today's society.
[0003] Graphene conductive coating solution is a new method for preparing high-conductivity composite materials, which is currently attracting widespread public attention. Its preparation is relatively simple and does not require harsh preparation conditions such as high temperature or vacuum. It only needs to be coated on the metal substrate at room temperature so that the coating solution forms a layer of conductive coating on the metal surface, which can effectively improve the current carrying capacity of the metal matrix and improve the electron transmission efficiency, thereby making the prepared composite material have good high conductivity properties. It can cleverly solve the main problems faced by the industry and has huge commercial potential and practical application value.
[0004] However, graphene conductive coating solutions on the market often have problems such as unstable dispersion of the coating solution, poor dispersion effect, and easy agglomeration of graphene. After coating, the bonding strength between the coating and the copper wire will be seriously affected, which will indirectly lead to a series of problems such as uneven distribution of graphene on the surface of the copper wire and poor continuity. As a result, the graphene coating on the surface of the copper wire cannot form a stable and continuous conductive network, which in turn affects the conductive properties of the graphene / copper composite wire.
[0005] Surfactants, as an additive to optimize the dispersion effect of coating solutions, can effectively solve the problems of difficult dispersion and easy agglomeration of graphene in existing coating solutions. Surfactants are mainly composed of three types: anionic, cationic and non-ionic. They are widely used in household cleaners, pesticide preparations, mining, personal care products, textiles, paints, oil production, papermaking industry and other fields. Summary of the invention
[0006] The technical problems to be solved by the present invention are: the dispersion of the carbon-based conductive coating solution is unstable, the conductivity is not significantly improved, and the surface roughness of the graphene copper composite wire after coating is large, the graphene sheets are warped, the adhesion is not strong, and it is easy to fall off.
[0007] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:
[0008] An electrostatic attraction type graphene conductive coating solution comprises the following components by weight percentage:
[0009] Graphene 1.0-2.0%, anionic surfactant 0.1-0.2%, cationic surfactant 0.1-0.2%, solvent 94.0-96.0%, and the balance is auxiliary additives.
[0010] As an improvement, the tap density of the graphene is less than 0.1 g / cm 3 , with a specific surface area of 530-580m 2 / g, particle size﹤10.0μm, pH is 6.0-8.0.
[0011] As an improvement, in the graphene, the mass fraction of carbon is ≥98%, the mass fraction of water is <1.0%, the mass fraction of chlorine is <1.0%, and the mass fraction of sulfur is <0.1%.
[0012] As an improvement, the anionic surfactant includes alkylbenzene sulfonate, alkyl sulfonate ester salt, alkyl sulfonate, alkyl sulfate, and fluorine-containing fatty acid salt.
[0013] As an improvement, the cationic surfactant includes fatty amine salts, ethanolamine salts and polyethylene polyamine salts.
[0014] The preparation method of the present invention comprises the following steps:
[0015] S1. The anionic surfactant and the cationic surfactant are placed in two containers, and equal amounts of the agent and the solvent are added to the two containers, respectively, and the liquids in the two containers are stirred;
[0016] S2. After the stirring is completed, the solutions in the two containers are mixed and then placed in an ultrasonic crusher for ultrasonic crushing.
[0017] As an improvement, the stirring in step S1 is magnetic stirring, the rotation speed of the magnetic stirring is 1200-2000 r / min, and the stirring time is 15-20 h.
[0018] As an improvement, the power of the ultrasonic crushing in step S2 is 35-45%, the ultrasonic crushing time is 1 hour, and the ultrasonic crushing adopts an interval crushing method, with each ultrasonic crushing for 5 minutes and a pause of 10 minutes.
[0019] The advantages of the present invention are:
[0020] 1. The present invention adds a surfactant to the solution, and utilizes the property that the surfactant can form micelles in the solution to reduce the surface tension of the solution. In addition, the strong electrostatic repulsion of the surfactant can weaken the van der Waals force between graphene sheets to a certain extent, prevent graphene from agglomerating in the coating solution, and disperse the graphene in the solvent more evenly.
[0021] 2. The present invention uses anionic surfactants and cationic surfactants at the same time. During preparation, corresponding solutions are first prepared respectively. After mixing, the positive and negative charges ionized in the solution attract each other to cause chemical bonding between molecular chains, so that the adhesion between graphene sheets and between graphene and copper wire is more firm, the surface roughness of the coating is effectively reduced, the graphene sheets are not easy to fall off, and the good continuity of graphene in the coating is maintained.
[0022] 3. After coating, the present invention has a firm bond between graphene and the copper wire, and has better arrangement and continuity on the surface of the copper wire, which greatly improves the "curling" defect of graphene caused by poor dispersion and other problems, and helps to improve the current carrying capacity of the copper wire and improve the conductivity of the copper wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Scanning electron microscope (SEM) morphology of a coating of a copper wire surface coated with a prior art graphene conductive coating solution.
[0024] Figure 2 Scanning electron microscope (SEM) morphology of a copper wire surface coated with the electrostatic attraction type graphene conductive coating solution of the present invention.
[0025] Figure 3 Surface morphology of a copper conductor coated with a prior art graphene conductive coating solution.
[0026] Figure 4 Surface morphology of a copper wire surface coated with the electrostatically attracted graphene conductive coating solution of the present invention. DETAILED DESCRIPTION
[0027] For the purpose of the following detailed description, it should be understood that the present invention may adopt various alternative changes and step sequences, unless expressly specified to the contrary. In addition, except in any operating examples, or otherwise indicated, all numbers representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values that vary according to the desired performance to be obtained by the present invention. At least it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.
[0028] In the following examples, the tap density of the graphene used is ﹤0.1g / cm 3 , with a specific surface area of 530 to 580 m 2 / g, particle size <10.0μm, pH 6.0-8.0; in the graphene, the mass fraction of carbon is ≥98%, the mass fraction of water is <1.0%, the mass fraction of chlorine is <1.0%, and the mass fraction of sulfur is <0.1%; the types of anionic surfactants can be alkylbenzene sulfonates, alkyl sulfonate salts, alkyl sulfonates, alkyl sulfates, fluorinated fatty acid salts, etc.; the types of cationic surfactants can be fatty amine salts, ethanolamine salts and polyethylene polyamine salts, etc., and the remaining conductive agents, binders, etc. are added by themselves, and the total is 100wt.%.
[0029] Example 1
[0030] This embodiment discloses an electrostatic attraction type graphene conductive coating solution, the raw materials of which include the following components by weight percentage:
[0031] Graphene 2.0%, anionic surfactant 0.1%, cationic surfactant 0.1%, solvent 95.0%, conductive agent polyaniline 1.8%, acrylic resin 1.0%.
[0032] In this embodiment, the anionic surfactant is sodium dodecylbenzene sulfonate; the cationic surfactant is hexadecyltrimethylammonium bromide.
[0033] The preparation method of this embodiment includes the following steps:
[0034] S1. Place anionic surfactant and cationic surfactant into two containers respectively, and add equal amounts of reagents and solvents into the two containers respectively, and perform magnetic stirring treatment on the liquids in the two containers respectively; the speed of magnetic stirring is 1200-2000r / min, and the stirring time is 15-20h.
[0035] S2. After stirring, the solutions in the two containers are mixed and then placed in an ultrasonic crusher for ultrasonic crushing. The power of ultrasonic crushing is 35-45%, the ultrasonic crushing time is 1 hour, and the ultrasonic crushing adopts an interval crushing method, with each ultrasonication for 5 minutes and a pause of 10 minutes.
[0036] After the preparation is completed, the prepared coating solution is poured into the filling tank, and the copper wire with a diameter of 0.2 mm is coated by a machine. The coating thickness of the silver-graphene copper composite wire is about 3 μm. The conductivity of the silver-graphene composite wire after coating is shown in Table 1.
[0037] Example 2
[0038] This embodiment discloses an electrostatic attraction type graphene conductive coating solution, the raw materials of which include the following components by weight percentage:
[0039] Graphene 2.0%, anionic surfactant 0.1%, cationic surfactant 0.1%, solvent 95.0%, conductive agent pyrene carboxylic acid 1.8%, acrylic resin 1.0%.
[0040] In this embodiment, the anionic surfactant is sodium dodecylbenzene sulfonate; the cationic surfactant is hexadecyltrimethylammonium bromide.
[0041] The preparation method of this embodiment is the same as that of embodiment 1.
[0042] The prepared coating solution was poured into the filling tank, and the copper wire with a diameter of 0.2 mm was plated by a machine. The coating thickness of the silver-graphene copper composite wire was about 3 μm. The conductivity of the silver-graphene composite wire after coating is shown in Table 1.
[0043] Example 3
[0044] This embodiment discloses an electrostatic attraction type graphene conductive coating solution, the raw materials of which include the following components by weight percentage:
[0045] Graphene 2.0%, anionic surfactant 0.1%, cationic surfactant 0.1%, solvent 95.0%, conductive agent polyaniline 1.8%, sodium carboxymethyl cellulose 1.0%.
[0046] In this embodiment, the anionic surfactant is sodium dodecylbenzene sulfonate; the cationic surfactant is hexadecyltrimethylammonium bromide.
[0047] The preparation method of this embodiment is the same as that of embodiment 1.
[0048] The prepared coating solution was poured into the filling tank, and the copper wire with a diameter of 0.2 mm was plated by a machine. The coating thickness of the silver-graphene copper composite wire was about 3 μm. The conductivity of the silver-graphene composite wire after coating is shown in Table 1.
[0049] The conductivity of the silver graphene conductive coating solution prepared in Examples 1-3 of the present invention was calculated by the following method:
[0050] The resistance was measured using a TX-1000A intelligent metal conductor resistivity meter, and the resistivity of the sample was calculated according to the formula ρ=R*S / L. The conductivity was then calculated according to the conductivity (%IACS)=0.017241 / ρ*100%.
[0051] Where R: product resistance value Ω; ρ-resistivity, Ω·mm 2 The test results of the silver graphene conductive coating solutions prepared in Examples 1-3 of the present invention are shown in Table 1.
[0052] Table 1 Test results of conductivity performance of the products prepared in Examples 1-3 of the present invention
[0053]
[0054] The present invention also provides a comparison example:
[0055] Comparative Example 1
[0056] The difference between Control Example 1 and Example 1 is that neither anionic surfactant nor cationic surfactant is added. The other components are the same as those in Example 1.
[0057] After the preparation, the copper wire was plated, and 5 meters of the plated graphene copper composite wire was taken for conductivity testing, and the sample was evenly divided into 5 sections, each section was 1 meter long, thus obtaining 5 experimental samples. The test results are shown in Table 2.
[0058] Table 2 Comparison of conductivity properties of copper wires plated with a plating solution without anionic and cationic surfactants before and after plating
[0059]
[0060] Comparative Example 2
[0061] The difference between Control Example 2 and Example 1 is that no cationic surfactant is added, and only anionic surfactant is added. The other components are the same as those in Example 1.
[0062] After the preparation, the copper wire was plated, and 5 meters of the plated graphene copper composite wire was taken for conductivity testing, and the sample was evenly divided into 5 sections, each section was 1 meter long, thus obtaining 5 experimental samples. The test results are shown in Table 3.
[0063] Table 3 Comparison of conductivity properties of copper wires before and after plating using a plating solution containing only anionic surfactants
[0064]
[0065] Comparative Example 3
[0066] The difference between Control Example 3 and Example 1 is that no anionic surfactant is added, and only a cationic surfactant is added. The other components are the same as those in Example 1.
[0067] After the preparation, the copper conductor was plated, and 5 meters of the plated graphene copper composite wire was taken for conductivity test, and the sample was evenly divided into 5 sections, each section was 1 meter long, thus obtaining 5 experimental samples. The test results are detailed in Table 4.
[0068] Table 4 Comparison of conductivity properties of copper wires plated with a plating solution containing only cationic surfactants before and after plating
[0069]
[0070] Comparative Example 4
[0071] The preparation process and raw materials used in Control Example 4 are the same as those in Example 1, and anionic and cationic surfactants are added simultaneously to prepare the coating solution.
[0072] After the preparation, the copper wire was plated, and 5 meters of the plated graphene copper composite wire was taken for conductivity test, and the sample was evenly divided into 5 sections, each section was 1 meter long, thus obtaining 5 experimental samples. The test results are detailed in Table 5.
[0073] Table 5 Comparison of conductivity properties of copper wires plated with a plating solution containing anionic and cationic surfactants before and after plating
[0074]
[0075] From the comparison of the data in Tables 2-5, it can be seen that the conductivity of the copper wire is significantly improved after being coated with the electrostatic attraction type graphene conductive coating solution of the present invention.
[0076] Combined with Figure 1 , Attachment Figure 2 It can be seen that the electrostatic attraction type conductive coating solution of the present invention can significantly improve the distribution state of graphene sheets on the surface of the copper wire and build a stable and continuous conductive network.
[0077] Depend on Figure 3 , Figure 4 It can be seen that the electrostatic attraction conductive coating solution of the present invention significantly improves the problem of graphene flakes curling on the surface of copper wire. The graphene curling amplitude is small, the coating surface is smooth, and the continuity between graphene flakes is good, which is conducive to the transmission of free electrons in the copper wire.
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An electrostatic attraction type graphene conductive coating solution, characterized in that: The composition includes the following components by weight percentage: Graphene 1.0-2.0%, anionic surfactant 0.1-0.2%, cationic surfactant 0.1-0.2%, solvent 94.0-96.0%, and the balance is auxiliary additives.
2. The electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: The tap density of the graphene is less than 0.1 g / cm 3 , with a specific surface area of 530-580m 2 / g, particle size﹤10.0μm, pH is 6.0-8.
0.
3. The electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: In the graphene, the mass fraction of carbon is ≥98%, the mass fraction of water is <1.0%, the mass fraction of chlorine is <1.0%, and the mass fraction of sulfur is <0.1%.
4. The electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: The anionic surfactants include alkylbenzene sulfonates, alkyl sulfonate esters, alkyl sulfonates, alkyl sulfates, and fluorine-containing fatty acid salts.
5. The electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: The cationic surfactants include fatty amine salts, ethanolamine salts and polyethylene polyamine salts.
6. The electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: The auxiliary additives include conductive agents and adhesives.
7. A method for preparing the electrostatic attraction type graphene conductive coating solution according to claim 1, characterized in that: The steps include: S1. The anionic surfactant and the cationic surfactant are placed in two containers, and equal amounts of the agent and the solvent are added to the two containers, respectively, and the liquids in the two containers are stirred; S2. After the stirring is completed, the solutions in the two containers are mixed and then placed in an ultrasonic crusher for ultrasonic crushing.
8. The method for preparing an electrostatic attraction type graphene conductive coating solution according to claim 7, characterized in that: The stirring in step S1 is performed by magnetic stirring, the rotation speed of the magnetic stirring is 1200-2000 r / min, and the stirring time is 15-20 h.
9. The method for preparing an electrostatic attraction type graphene conductive coating solution according to claim 7, characterized in that: The power of the ultrasonic crushing in step S2 is 35-45%, the ultrasonic crushing time is 1 hour, and the ultrasonic crushing adopts an interval crushing method, with each ultrasonic crushing for 5 minutes and a pause of 10 minutes.